State-of-the-art: functional ﬂuorescent probes for bioimaging and pharmacological research - Lu Lu; Wu Zhou-yue; Li Xin; Han Feng (Acta Pharmacologica Sinica; Vol 40, No 6 (June 2019): Acta Pharmacologica Sinica, 2019)
Cardiovascular diseases, neuropsychiatric disorders, and cancers seriously endanger human health. Mechanistic and pharmacological mechanisms of candidate drugs are central to the translational paradigm. Since many signal transduction and molecular events are implicated in these diseases, a novel method to interrogate the key pharmacological mechanisms is required to accelerate innovative drug discovery. Much attention now focuses on the real-time visualization of molecular disease events to yield new insights to the pathogenesis of the diseases. This review focuses on recent advances in the development of chemical probes for imaging pathological events to facilitate the study of the underlying pharmacodynamics and toxicity involved. As reviewed here, optical imaging is now frequently viewed as an indispensable technique in the ﬁeld of biological research. Promoting interdisciplinary collaboration among chemistry, biology and medicine, is necessary to further reﬁne functional ﬂuorescent probes for diagnostic and therapeutic applications.